Multifocal Aggressive Squamous Cell Carcinomas Induced by Prolonged Voriconazole Therapy: A Case Report. (28th November 2010) - Morice, C.; Acher, A.; Soufir, N.; Michel, M.; Comoz, F.; Leroy, D.; Verneuil, L.
Abstract : Voriconazole is a treatment for severe fungal infections. Prolonged voriconazole therapy may induce skin reactions, with 1% of severe photosensitivity accidents. Recently the imputability of voriconazole in skin carcinogenesis has been suggested. This report concerns a 55-year-old man suffering from pulmonary aspergillosis who presented a phototoxic reaction a few months after introduction of voriconazole, followed by multiple squamous cell carcinomas of sun-exposed skin areas. After voriconazole discontinuation, no new carcinoma was observed. The detection of EBV and HPV in skin lesions was negative. Exploration of gene mutations involved in skin carcinogenesis showed two variants of the MICR gene. The occurrence of multiple, recurrent, aggressive squamous cell carcinomas is rare with voriconazole, but its imputability is strongly suggested. A plausible hypothesis is that several factors including voriconazole uptake, immunosuppression, and genetic background could explain the phenotype of fast-developing skin carcinomas. Voriconazole therapy should be accompanied by stringent photoprotection and skin monitoring.